Supporting Sustainability and Social Responsibility through the Implementation of ESG Principles in Non-Bank Financial Institutions - Muhamad Randi Riswanda (Generate Digital Publishing, 2025)
Objectives: This study aims to analyze the integration of Environmental, Social, and Governance (ESG) principles in non-bank financial institutions (NBFIs) in Indonesia and its impact on the sustainability and competitiveness of the financial sector. The primary focus of the study is to examine the impact of ESG implementation on financial stability, risk mitigation, and compliance with relevant regulations. Research Design & Methods: This study uses a qualitative approach with literature study methods and regulatory analysis to explore ESG practices in NBFIs. Data sources include annual reports, regulatory policies such as those from the Financial Services Authority (OJK), as well as academic and industry studies related to ESG implementation in the non-bank financial sector. Findings: The study's results indicate that ESG implementation in NBFIs enhances efficiency, attracts sustainability-focused investors, and fosters greater transparency. Technologies such as big data, blockchain, and AI enhance ESG performance; however, reporting diversity and regulatory complexity remain significant challenges. Implications & Recommendations: Enhancing ESG effectiveness in NBFIs requires structured regulations, standardized reporting for transparency, and optimized digital technology adoption. Strengthening ESG-based risk management strategies is essential for ensuring long-term sustainability. Contribution & Value Added: This study contributes by providing insights into the role of ESG in improving the competitiveness and financial stability of NBFIs in Indonesia. This study also highlights the importance of digital innovation in supporting ESG implementation. It provides policy recommendations for regulators and industry stakeholders to enhance the sustainability of the non-bank financial sector.